Single-molecule toxicogenomics: Optical genome mapping of DNA-damage in nanochannel arrays - Detinis Zur, Tahir; Margalit, Sapir; Jeffet, Jonathan; Grunwald, Assaf; Fishman, Sivan; Tulpová, Zuzana; Michaeli, Yael; Deek, Jasline; Ebenstein, Yuval (DNA repair, 2025)
Quantitative genomic mapping of DNA damage may provide insights into the underlying mechanisms of damage and repair. Sequencing based approaches are bound to the limitations of PCR amplification bias and read length which hamper both the accurate quantitation of damage events and the ability to map them to structurally complex genomic regions. Optical Genome mapping in arrays of parallel nanochannels allows physical extension and genetic profiling of millions of long genomic DNA fragments, and has matured to clinical utility for characterization of complex structural aberrations in cancer genomes. Here we present a new mapping modality, Repair-Assisted Damage Detection - Optical Genome Mapping (RADD-OGM), a method for single-molecule level mapping of DNA damage on a genome-wide scale. Leveraging ultra-long reads to assemble the complex structure of a sarcoma cell-line genome, we mapped the genomic distribution of oxidative DNA damage, identifying regions more susceptible to DNA oxidation. We also investigated DNA repair by allowing cells to repair chemically induced DNA damage, pinpointing locations of concentrated repair activity, and highlighting variations in repair efficiency. Our results showcase the potential of the method for toxicogenomic studies, mapping the effect of DNA damaging agents such as drugs and radiation, as well as following specific DNA repair pathways by selective induction of DNA damage. The facile integration with optical genome mapping enables performing such analyses even in highly rearranged genomes such as those common in many cancers, a challenging task for sequencing-based approaches.
Keywords: mikrofluidní analytické techniky; DNA Copy Number Variations; bromičnany; Microfluidic Analytical Techniques; Humans; nádorové buněčné linie; nanotechnologie; oxidační stres; regulace genové exprese; Gene Expression Regulation; Nanotechnology; toxikogenetika; poškození DNA; DNA Damage; Bromates; Oxidative Stress; Toxicogenetics; zobrazení jednotlivé molekuly; mapování chromozomů; stanovení celkové genové exprese; lidé; Gene Expression Profiling; DNA Repair; oprava DNA; Single Molecule Imaging; Cell Line, Tumor; Chromosome Mapping; variabilita počtu kopií segmentů DNA